PREVALENCE OF ANEMIA AND ITS ASSOCIATION WITH BODY MASS INDEX AND PLASMA PROTEIN IN MEDICAL STUDENTS OF KOLHAN REGION OF JHARKHAND – A CROSSSECTIONAL STUDY - CHOUDHARY, NEELAM; MAHATO, PARAS NATH; SINGH, UMA SHANKAR; RAJAN KUMAR BARNWAL; KUMAR VIMAL; KUBER CHANDRA SETUA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Anemia is one of the major public health concerns affecting almost 30% of the global population. Past studies have indicated that anemia is linked to lower body mass index (BMI) and plasma protein levels. This study aims to determine the prevalence of anemia among medical students and also to investigate its association with BMI and plasma proteins. Methods: A cross-sectional study of 177 medical and paramedical students aged 18–21 years was done at MGM Medical College in Jamshedpur from September 2018 to July 2019. A Transasia EM200 automated chemical analyzer was used to identify plasma protein using the biuret approach. HemoCOR-D (cyanmethemoglobin) was quantified by a colorimetric instrument. A colorimetric apparatus measured hemoglobin (Hb) with HemoCOR-D (cyanmethemoglobin). Results: There are a total of 177 pupils. The study included 48% (n=85) females and 52% (n=92) males. Males had a mean age of 20.03± 0.99 years while females had a mean age of 20.16±0.937 years. Males had greater Hb levels and protein levels than females, with averages of 13.61 ± 1.43 and 7.77± 0.93, respectively. Males had a frequency of anemia of 15.4%, while females had a prevalence of 70.9%. The researchers discovered a statistically significant link between anemic and non-anemic girls’ plasma protein levels (p=0.07), protein intake and plasma protein (p=0.048), and BMI and Hb (p=0.022). Conclusions: A significant association was found between daily protein intakes with plasma protein. The association between BMI and hemoglobin was also found significant.